If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(8)(x + 3) + log(8) * 3x = log(8) Reorder the terms: glo * 8(3 + x) + log(8) * 3x = log(8) Reorder the terms for easier multiplication: 8glo(3 + x) + log(8) * 3x = log(8) (3 * 8glo + x * 8glo) + log(8) * 3x = log(8) (24glo + 8glox) + log(8) * 3x = log(8) Reorder the terms for easier multiplication: 24glo + 8glox + 8 * 3glo * x = log(8) Multiply 8 * 3 24glo + 8glox + 24glo * x = log(8) Multiply glo * x 24glo + 8glox + 24glox = log(8) Combine like terms: 8glox + 24glox = 32glox 24glo + 32glox = log(8) Reorder the terms for easier multiplication: 24glo + 32glox = 8glo Solving 24glo + 32glox = 8glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8glo' to each side of the equation. 24glo + -8glo + 32glox = 8glo + -8glo Combine like terms: 24glo + -8glo = 16glo 16glo + 32glox = 8glo + -8glo Combine like terms: 8glo + -8glo = 0 16glo + 32glox = 0 Factor out the Greatest Common Factor (GCF), '16glo'. 16glo(1 + 2x) = 0 Ignore the factor 16.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Add '-2x' to each side of the equation. 2x + -2x = -1 + -2x Combine like terms: 2x + -2x = 0 0 = -1 + -2x Simplifying 0 = -1 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 21=8p^2-2p | | 3x-7=2(ax-5) | | 4x^2-13x+14=2x+5 | | 3+4s=10+2s | | 10*5+x=80 | | h=mp+c | | 5(2x-2)=-20 | | 46x+1996=3200 | | x^3-3x^2-2=0 | | h^2+17h+72=0 | | 6(4+3x)=7(x-1)+1 | | x-(5/5)+10=w | | 6x^2-7-3=0 | | 2w+2(2w-7)=10 | | -2=-3+2+7x | | x-(5/5)+10=x | | 3y-xy= | | 7x+3=9-(5x-7) | | -2=-3x+2+2+7x | | 5(6+n)=50 | | 3-0/5=x | | x=0/10(2/1) | | (24+11)*w=x | | 52=c+18 | | 12x^3+24-36x=0 | | x=0/10(2) | | -14-4=13y-14-12y | | -150=-10(3b) | | -a^2-6a-9=0 | | -8y^3+5y^3= | | 4(x+1)=5+6x | | 4x=2x+36 |